Intergovernmental organizations (IGOs) as relevant actors in International Relations - Olter Castillo, Agnieszka (2021)
Since the end of the Second World War, scholars in International Relations focused more on the role that non-state actors, like intergovernmental organizations (IGOs), have in shaping the global order. The following document analyzes some global, regional, and subject-specific IGOs and their role in the international system.